PENGARUH SOSIALISASI DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK SESUDAH PENDAERAHAN PBB-P2 DENGAN KONTROL PETUGAS KELURAHAN SEBAGAI VARIABEL MODERATING DI KOTAMADYA SURABAYA - FACHRU ANNISA, KARTIKA (Jurnal Akuntansi AKUNESA, 2016)
Abstract This research aims to examine the effect of socialization and tax konowledge to taxpayer’s compliance with urban village officer’s control as a moderating variable in Surabaya city. This research used quantitave approach with the primary data obtained from questionnaires. The sampling method of this research used purposive sampling with a sample of 110 respondent from land and building taxpayers in Surabaya city. This research used Moderated Regression Analysis (MRA) using SPSS 21. The result of this research shows that the socialization influenced taxpayer’s compliance and the control of urban village officer can moderate the relation  of socialization and taxpayer’s compliance. Furthermore, the tax knowledge  influenced taxpayer’s compliance but the control of urban village officer can’t moderate the relation  of tax knowledge and taxpayer’s compliance.   Keywords : Taxpayer’s Compliance, Socialization, Tax Knowledge, Urban Village Officer’s Control